Strengthening the skills of women farmer groups in the production and formulation of lemongrass essential oil - Setiana, Mira; Ferawati, Bangkit Ina; Marfuah, Hasti Hasanati; 'Azizah, Alfi Rohmatul; Nugroho, Raihan Alfian (Community Empowerment, 2025)
Limited technical knowledge in distillation processes and product formulation has hindered the economic optimization of lemongrass among the Tanjung Asri Women Farmer Group (KWT). This community service program aims to enhance the technical capacity of KWT members through a sciencepreneurship approach, integrating extraction, purification, and product stability processes. The methodology employed participatory training, equipment demonstrations, and hands-on production practice. Results showed a significant increase in participants' technical understanding from 72.5% to 91.3%, with 80% of participants becoming proficient in independent distillation equipment operation. The implemented process innovation successfully increased oil yield by ±20%, producing clearer and more stable essential oil. Overall, the program fostered product downstreaming and business diversification based on lemongrass essential oil as a driver for sustainable local economic development.